2021
DOI: 10.1507/endocrj.ej20-0734
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genome-wide DNA methylation patterns in obesity

Abstract: Obesity is a chronic and complex psychosomatic disease that is becoming increasingly prevalent worldwide. This study aimed to analyze whole methylation profiles to uncover the epigenetic mechanisms associated with obesity. DNA methylation profiles in blood samples from patients with obesity and normal controls were studied using the Illumina 850 K methylation microarray. The diagnostic value of the differentially methylated genes was determined using receiver operating characteristic (ROC) analysis. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
3
1
1
Order By: Relevance
“…Calcium signaling could be involved in the neural control of hunger and energy metabolism as well as in the gut–brain axis [ 52 , 53 ]. In line with our study, another genome-wide DNA methylome study conducted on people with obesity reported calcium-signaling among the top five enriched pathways [ 54 ].…”
Section: Discussionsupporting
confidence: 89%
“…Calcium signaling could be involved in the neural control of hunger and energy metabolism as well as in the gut–brain axis [ 52 , 53 ]. In line with our study, another genome-wide DNA methylome study conducted on people with obesity reported calcium-signaling among the top five enriched pathways [ 54 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that the differential methylation signal of SOSTDC1 gene was ranked at the top, and combined with the expression characteristics of SOSTDC1 gene, we suggest that differential methylation of SOSTDC1 is the main reason for differential expression of the SOSTDC1 gene, and consequently the formation of the ALC wool type. Indeed, in the studies related to genome-wide methylation analysis to date, the significantly differential methylation sites tend to be scattered across chromosomes [ 52 55 ], however, in this study, the differentially methylated sites were concentrated in one gene and the signals were much more significant than other sites in the genome. This result is most likely due to three reasons: first, the samples tested are siblings with a relatively consistent genetic background, second, the target characteristics are distinctly different and the time points and body parts where the samples were collected are precisely consistent among individuals, and finally, there does exist a CpG island on the second exon of sheep SOSTDC1 gene (Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Hence, we concentrated only on the CpG sites with an absolute mean β difference > 0.1 (Table 1). Interestingly, several of these ethnically differentiated sites were previously reported for their association with common diseases, for instance, cg09789536 for cow's milk allergy [40], cg07157834 and cg25629442 for Alzheimer's disease [41,42], cg09894276 for obesity [43], and cg04635334 for depression [44]. Moreover, 9 of the 23 CpG sites had a cis or trans methylation quantitative trait loci [45], suggesting that genome variation plays a non-negligible role in shaping ethnic differences in DNA methylation pattern among closely related populations, as previously validated in inter-continental human populations.…”
Section: Differences In Genome-wide Dna Methylation Levels At the Cpg...mentioning
confidence: 99%